Social and emotional wellbeing assessment instruments for use with Indigenous Australians: A critical review. (August 2017) - Le Grande, M.; Ski, C.F.; Thompson, D.R.; Scuffham, P.; Kularatna, S.; Jackson, A.C.; Brown, A.
Abstract: Rationale: There is growing recognition that in addition to universally recognised domains and indicators of wellbeing (such as population health and life expectancy), additional frameworks are required to fully explain and measure Indigenous wellbeing. In particular, Indigenous Australian wellbeing is largely determined by colonisation, historical trauma, grief, loss, and ongoing social marginalisation. Dominant mainstream indicators of wellbeing based on the biomedical model may therefore be inadequate and not entirely relevant in the Indigenous context. It is possible that "standard" wellbeing instruments fail to adequately assess indicators of health and wellbeing within societies that have a more holistic view of health. Objective: The aim of this critical review was to identify, document, and evaluate the use of social and emotional wellbeing measures within the Australian Indigenous community. Method: The instruments were systematically described regarding their intrinsic properties (e.g., generic v. disease-specific, domains assessed, extent of cross-cultural adaptation and psychometric characteristics) and their purpose of utilisation in studies (e.g., study setting, intervention, clinical purpose or survey). We included 33 studies, in which 22 distinct instruments were used. Results: Three major categories of social and emotional wellbeing instruments were identified: unmodified standard instruments (10), cross-culturally adapted standard instruments (6), and Indigenous developed measures (6). Recommendations are made for researchers and practitioners who assess social and emotional wellbeing in Indigenous Australians, which may also be applicable to other minority groups where a more holistic framework of wellbeing is applied. Conclusion: It is advised that standard instruments only be used if they have been subject to a formal cross-cultural adaptation process, and Indigenous developed measures continue to be developed, refined, and validated within a diverse range of research and clinical settings. Highlights: Indigenous wellbeing is best understood within a holistic framework. Historical trauma and grief are strong determinants of current wellbeing. A construct of social and emotional wellbeing (SEWB) is most appropriate. Cross-cultural adaptation of existing wellbeing instruments is required. Further work is required to develop valid SEWB instruments for Indigenous people.